A Study on Customer Retention and Brand Image: An Empirical Evidence of Mobile Operators in Bangladesh - Chowdhury, Md Rakeullah (Asian Journal of Empirical Research, 2020)
Due to increasing competition and the opportunity to change subscribers, customer retention has become the most challenging job for the mobile telecommunication service providers in Bangladesh. This study is carried out to know the relation between customer retention and activities related to brand image undertaken by mobile telecommunication organizations. A Likert Scale of five dimensions was utilized to collect data from the subscribers with a structured questionnaire. A convenient sampling method was utilized. Reliability test, KMO & Bartlett’s test were carried out to identify the statistical significance of data. An exploratory factor analysis (EFA) performed to find out latent variables. Finally, linear regression was measured to test the hypothesis. Firstly two latent variables named brand positivity and brand familiarity were found from factor analysis and then it was shown that these two variables are positively associated with customer retention.